ספרות כפעולת טרור: חירות ויצירה בכתביה של לאה איני - שוורץ יגאל (מכאן, 2016)
Lea Aini’s father was a Holocaust survivor from Salonika. This is an explosive biographical-psychological and socio-cultural matter, since it was deemed inferior and obscure in the context in which Aini grew up. Uncovering this explosive matter and its role in Aini’s characters’ world is necessary in the attempt to understand the writer’s artistic urge and its products. Aini’s poetic style is the result of a persistent, brave attempt to escape the unique world-image she absorbed as a child, created by the merging of two ‘second generation’ syndromes normally separated within Israeli society: the second generation of Holocaust survivors and the second generation of ‘olim’ (new immigrants) from communities perceived by the Ashkenazi hegemony as weak and inferior. The article presents three arguments: First, that Aini ‘inherited’ her father’s worldview, forced upon him by his experiences in Auschwitz, and that it is modeled as a Panopticon - a closed space in which there is a central supervisory authority and a supervised crowd. The second argument is that Aini projected this Panopticon model onto her world - the State of Israel in the 1960s, 1970s and 1980s - and that this has an economic significance reflected in a dichotomy between those who hold economic and symbolic capital and those whose way to owning capital is blocked. The third argument, based on the first two, is that Aini developed resistant literary practices through which she dealt with the systematic silencing, erasing and standardizing practices of the supervising institution, led by ‘belles-lettres’.